Peritubular myoid cells from rat seminiferous tubules contain actin and myosin filaments distributed in two independent layers - Losinno, Antonella Denise (2012)
In the mammalian testis, peritubular myoid cells (PM cells) surround the seminiferous tubules (STs), express cytoskeletal markers of true smooth muscle cells, and participate in the contraction of the ST. It has been claimed that PM cells contain bundles of actin filaments distributed orthogonally in an intermingled mesh. Our hypothesis is that these actin filaments are not forming a random intermingled mesh, but are actually arranged in contractile filaments in independent layers. The aim of this study is to describe the organization of the actin cytoskeleton in PM cells from adult rat testes and its changes during endothelin-1-induced ST contraction. For this purpose, we isolated segments of ST corresponding to the stages IX-X of the spermatogenic cycle (ST segments), and analyzed the actin and myosin filament distribution by confocal and transmission electron microscopy. We found that PM cells have actin and myosin filaments interconnected in thick bundles (AF-MyF bundles). These AF-MyF bundles are distributed in two independent layers: an inner layer toward the seminiferous epithelium, and an outer layer toward the interstitium, with the bundles oriented perpendicularly and in parallel to the main ST axis, respectively. In endothelin-1 contracted ST segments, PM cells increased their thickness and reduced their length in both directions, parallel and perpendicular to the main ST axis. The AF-MyF bundles maintained the same organization in two layers, although both layers appeared significantly thicker. We believe that this is the first time this arrangement of AF-MyF bundles in two independent layers has been shown in smooth muscle cells, and that this organization would allow the cell to generate contractile force in two directions.